Bahasa Inggris Bahasa Inggris: Bahasa Inggris - apriliyani, indah rosika; Muh. Syafei; Mutohhar (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2023)
The purpose of this research was to analyze the kind of online platform used by students teacher of EED UMK in the internship program and the problem of using online platform in internship program after covid 19 pandemic by students teacher. The research method use is qualitative. The data collection technique was carried out by the researcher using the questionnaire, interview, and documentation with fifteen seventh semester students teacher of EED UMK as a subject. Respondents said in internship program after pandemic the online platform used by students teacher are Google Meet, Google Classroom, Zoom, WhatsApp, Google Form, Padlet, Wordwall, Mentimeter. Google Classroom and Zoom are little used because the students not pay attention in the learning process and difficult to control the students, and WhatsApp become the most online platform by students teacher in internship program after pandemic, because easy and practice. The most problem faced by students teacher is network connection and the less problem is ability of students teacher in use online platform. The researcher suggestions the students teacher must learn about the online platform and select suitable online platform for students.